Individualized treatment response prediction of dialectical behavior therapy for borderline personality disorder using multimodal magnetic resonance imaging - Schmitgen, Mike; Niedtfeld, Inga; Schmitt, Ruth; Mancke, Falk; Winter, Dorina; Schmahl, Christian; Herpertz, Sabine (Brain and behavior, 2019)
Our work provides important new insights about treatment prediction in a specific mental disorder of high clinical relevance that is borderline personality disorder, using random forest classification via pretreatment clinical and demographical (CD), functional, and structural magnetic resonance imaging (MRI) data from patients with borderline personality disorder (BPD) to predict individual treatment response.